Post‐SARS‐CoV‐2‐vaccination cerebral venous sinus thrombosis: an analysis of cases notified to the European Medicines Agency. (4th August 2021) - Krzywicka, Katarzyna; Heldner, Mirjam R.; Sánchez van Kammen, Mayte; van Haaps, Thijs; Hiltunen, Sini; Silvis, Suzanne M.; Levi, Marcel; Kremer Hovinga, Johanna A.; Jood, Katarina; Lindgren, Erik; Tatlisumak, Turgut; Putaala, Jukka; et al.
Abstract: Background and purpose: Cerebral venous sinus thrombosis (CVST) has been described after vaccination against SARS‐CoV‐2. The clinical characteristics of 213 post‐vaccination CVST cases notified to the European Medicines Agency are reported. Methods: Data on adverse drug reactions after SARS‐CoV‐2 vaccination notified until 8 April 2021 under the Medical Dictionary for Regulatory Activities Term 'Central nervous system vascular disorders' were obtained from the EudraVigilance database. Post‐vaccination CVST was compared with 100 European patients with CVST from before the COVID‐19 pandemic derived from the International CVST Consortium. Results: In all, 213 CVST cases were identified: 187 after AstraZeneca/Oxford (ChAdOx1 nCov‐19) vaccination and 26 after a messenger RNA (mRNA) vaccination (25 with Pfizer/BioNTech, BNT162b2, and one with Moderna, mRNA‐1273). Thrombocytopenia was reported in 107/187 CVST cases (57%, 95% confidence interval [CI] 50%–64%) in the ChAdOx1 nCov‐19 group, in none in the mRNA vaccine group (0%, 95% CI 0%–13%) and in 7/100 (7%, 95% CI 3%–14%) in the pre‐COVID‐19 group. In the ChAdOx1 nCov‐19 group, 39 (21%) reported COVID‐19 polymerase chain reaction tests were performed within 30 days of CVST symptom onset, and all were negative. Of the 117 patients with a reported outcome in the ChAdOx1 nCov‐19 group, 44 (38%, 95% CI 29%–47%) had died, compared to 2/10 (20%, 95% CI 6%–51%) in the mRNA vaccine group and 3/100 (3%, 95% CI 1%–8%) in the pre‐COVID‐19 group. Mortality amongst patients with thrombocytopenia in the ChAdOx1 nCov‐19 group was 49% (95% CI 39%–60%). Conclusions: Cerebral venous sinus thrombosis occurring after ChAdOx1 nCov‐19 vaccination has a clinical profile distinct from CVST unrelated to vaccination. Only CVST after ChAdOx1 nCov‐19 vaccination was associated with thrombocytopenia. Abstract : We used the EudraVigilance database of the European Medicines Agency to identify 213 CVST cases after COVID‐19 vaccination ‐ 187 after AstraZeneca/Oxford (ChAdOx1 nCov‐19) vaccination and 26 after a mRNA vaccination (25 with Pfizer/BioNTech [BNT162b2] and one with Moderna [mRNA‐1273]). Only CVST after vaccination with ChAdOx1 nCov‐19 was associated with thrombocytopenia. We compared post‐vaccination CVST to 100 European patients with CVST from before the COVID‐19 pandemic and showed that CVST occurring after ChAdOx1 nCov‐19 vaccination has a clinical profile distinct from CVST unrelated to vaccination.